The Impact of Regulation on Islamic Financial Institutions Toward the Monopolistic Practices in the Banking Industrial in Aceh, Indonesia - Fahmi, Chairul (Jurnal Ilmiah Peuradeun, 2023)
The ratification of Aceh regulation (Hereafter called Qanun) Number 11 of 2018 concerning Islamic Financial Institutions (Hereafter called Qanun LKS) has provided special rights for Islamic banking institutions, while non-Islamic banking institutions are not permitted to run their business in the province. At the same time, the central Government also decided to merge three state-owned Islamic banks, namely BNI Syariah, BRI Syariah, and Mandiri Syariah, to become Bank Syariah Indonesia (BSI). These policies have potentially violated Law on Antitrust, especially in Aceh Province. This article aimed to analyze whether the local Government's policy in enacting the Qanun LKS and consolidating the BSI is part of monopoly practices and unfair business competition in the banking sector in the Aceh region. This research was classified as normative qualitative research, where data was obtained from secondary sources, such as laws, books, journals and related studies. The results showed that the enactment of Qanun LKS has restricted conventional banking from expanding its business in the region. In addition, the Government’s policy to consolidate three state-owned Islamic banks, which control more than seventy-five of the market share in Aceh province, was considered contrary to the law on the Prohibition of Monopolistic Practices and Unfair Business Competition Number 5 of 1999.